Improving The Qualifications Of Teaching Staff In The Higher Education System – A New Approach To Education - Ashurova Feruza Akhmatovna (Genius Journals, 2025)
This article provides information on the methods of developing skills in organizing the teaching process in the system of continuous education and professional development, as well as improving the overall pedagogical competencies of teachers. It is also noted that the need to improve the skills of teaching staff in the higher education system is a key area for a quality educational process.
Keywords: modern pedagogical methods, continuing education, innovative technologies, higher education, professional development, education, digital learning platforms.